The Risks of Hemostaic Material in Tonsillectomy - Bar Ronen; Braverman Itzhak (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2015)
Importance: Surgicel is an effective hemostat either for intra or post-operative bleedings, but should be used cautiously in the case of tonsillectomy. Some surgeons choose to leave pieces of surgicel in the tonsils bed for a continuous haemostatic effect. The material when left in the tonsils fossa is no different than other foreign body and put the patient in a significant risk of suffocation.  Observations: four years old girl was admitted to the E.R with multiple complaints and rapid deterioration of her physical state few days after tonsillectomy. Bulky Haemostatic Material spheres almost completely blocked the oropharynx. The foreign material was removed and the complaints resolved, with full recovery.  Conclusions and Relevance: leaving surgicel impactions in the oropharynx upon completion of tonsillectomy operation should be avoided.